Dataset of a complete genome sequence of Vibrio owensii v2 isolated from diseased Sabah’s red algae seaweed, Kappaphycus alvarezii - Vernon Vest Manguna; Yong, Wilson Thau Lym; Mohd Faizal Abu Bakar; Nur Athirah Yusof (Elsevier Inc., 2025)
Kappaphycus alvarezii, a primary source of k-carrageenan, is a popular cuisine in Malaysia, particularly in Sabah. Recently, Vibrio owensii was detected in farmed K. alvarezii. V. owensii is a pathogen known to cause diseases in humans and is also an opportunistic pathogen affecting K. alvarezii, leading to reduced quality and yield of the seaweed. The genome sequence of V. owensii strain v2 was sequenced using the DNBSEQ-G400 platform. The genome is composed of two chromosomes, measuring 3,255,511 bp and 2,308,715 bp, with a G+C content of 45.6 % and 45.8 %, respectively. Phylogenomic analysis revealed that this genome strain shares 67 % similarity with other V. owensii strains genome. This reports the analysis of virulence factors, antimicrobial resistance genes, and other relevant categories to better understand the pathogenicity of V. owensii towards K. alvarezii.